Developing a strategic research framework for Sport and Exercise Medicine - Holtzhausen, L. J.; van Zyl, G. J.; Nel, M. M. (British Journal of Sports Medicine, 2014)
Background/aim: Sport and Exercise Medicine (SEM) is a young, fast growing discipline. The need to broaden its evidence base has been established. The aim of the study was to compile a research-based strategic framework for the development of a sustainable research programme in SEM at a South African university.